Private Higher Education in a Dominantly Public Sector: The Case of Germany - Kehm, Barbara (International Higher Education, 2022)
This article presents the role of private higher education in Germany. It includes some statistics about the size of the sector compared to the public sector, discusses motives for establishing and running a private higher education institution, and focusses on the public debates and perceptions about the private sector.